Learning Media for Islamic Religious Education during a Pandemic: Systematic Literature Review Analysis - Asdlori Asdlori (Indonesian Academy of Social and Religious Research (IASRR), 2023)
This study intends to analyze the learning media utilized for Islamic religious education in Indonesia during the Covid-19 pandemic. This study is a systematic literature review utilizing the Prisma methodology. Mendeley and Garuda article databases with limited articles published from 2020 to 2023 are utilized. Using the search terms